Middleware Integration for Financial Services and Banking: A Framework for Resilient Architecture - Jyothi Siva Rama Krishna Terli (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive framework for middleware integration in financial services and banking, examining the critical role of these technologies in facilitating real-time transaction processing, trade execution, and regulatory compliance. The article Dominant Middleware Platforms explores their distinctive capabilities and optimal use cases within financial environments. The article explores architectural patterns for financial message processing, emphasizing event-driven architectures and message reliability mechanisms that ensure transaction integrity. It examines strategies for building resilient financial infrastructure through high availability clusters, disaster recovery planning, and sophisticated failover mechanisms. The integration of real-time analytics for decision support is explored, highlighting advances in market data processing, algorithmic trading infrastructure, and AI-powered fraud detection. Finally, the article assesses future directions, including cloud migration, blockchain integration, and the transformative impact of artificial intelligence on financial middleware systems, providing financial institutions with a roadmap for technology selection and implementation.
Keywords: Financial middleware; event-driven architecture; transaction integrity; resilient infrastructure; real-time analytics